Controlled growth of large-area anisotropic ReS2 atomic layer and its photodetector application. Issue 45 (2nd November 2016) - Li, Xiaobo; Cui, Fangfang; Feng, Qingliang; Wang, Gang; Xu, Xiaosa; Wu, Juanxia; Mao, Nannan; Liang, Xing; Zhang, Zhongyue; Zhang, Jin; Xu, Hua
Abstract : A large-area anisotropic ReS2 monolayer film with superior photoelectric properties was synthesized via a space-confined growth approach. Abstract : As an anisotropic 2D layered material, rhenium disulfide (ReS2 ) has attracted much attention because of its unusual properties and promising applications in electronic and optoelectronic devices. However, the low lattice symmetry and interlayer decoupling of ReS2 make asymmetric growth and out-of-plane growth occur quite easily; therefore, thick flake, dendritic and flower-like structures of ReS2 have mostly been obtained previously. Here, we report on an approach based on space-confined epitaxial growth for the controlled synthesis of ReS2 films. Using this approach, large-area and high-quality ReS2 films with uniform monolayer thickness can grow on a mica substrate. Furthermore, the weak van der Waals interaction between the surface of mica and ReS2 clusters, which favors surface-confined growth while avoiding out-of-plane growth, is critical for growing ReS2 with uniform monolayer thickness. The morphological evolution of ReS2 with the growth temperature reveals that asymmetric growth can be suppressed at relatively low temperatures. A ReS2 field-effect transistor displayed a current on/off ratio of 10 6 and an electron mobility of up to 40 cm 2 V −1 s −1, with outstanding photoresponsivity of 12 A W −1 . This work not only promotes the large-scale employment of ReS2 in high-performance optoelectronic devices, but also provides a means of controlling the unusual growth behavior of low-lattice-symmetry 2D layered materials.